Bhabinkamtibmas Performance Through Community Development to Prevent Conflict Between Pencak Silat Colleges - Purwanto, Nady Kinanti (Advances in Police Science Research Journal, 2024)
Pencak silat as a traditional Indonesian martial art has cultural value and local wisdom. In Jombang Regency there are 24 registered pencak silat schools, but there has been an increase in conflicts between schools which have resulted in violence and casualties. This research aims to examine the performance of Bhabinkamtibmas (Bhayangkara Pembina Security and Community Order) in community development to prevent conflict between pencak silat schools in the Jombang Police area. This research uses a qualitative approach with a field research method, the focus of the research is the performance of Bhabinkamtibmas in coaching. The research results show that the conflict was triggered by friction between members of the lower ranks of the university due to the rapid development of followers among productive circles. Bhabinkamtibmas carries out prevention through a direct approach with counseling and visits. Inhibiting factors include operational budgets, multiple village duties, empty villages, and high follower growth. Supporting factors are leadership motivation, assistance from university leaders, and the Jombang Faithful Silat Association. Efforts to minimize this include collaboration between members of the university, Head of Division, Regional Government regarding the budget, as well as the Kasat Binmas award program for Bhabinkamtibmas.